(untitled) (مجلة إحالات, 2026)
Analytical linguistic philosophy emerged in the late 19th and early 20th centuries, using mechanisms of linguistic and linguistic analysis to address many of the exceptional philosophical problems that were caused by linguistics, embodied by the ambiguity of many terms and expressions surrounding the language of philosophy, they turned to linguistic analysis to remedy them. , and the emergence of the so-called Linguistic Turning, and this trend was a reaction to the control of idealism over philosophical thought, the analytical trend appeared reaction and anti Hegelianism philosophy. The other reason that supported this analytical trend is the development of mathematical and natural sciences and their approaches that have gone from intuition to experimentation this approach that is characterized by precision and clarity, so philosophy has gone to analysis as an alternative scientific procedure that can find logical solutions, so the new philosophy is described as analytical , the difficulty of philosophical expressions cannot be overcome by the dismantling of linguistic forms to understand their components and then re-reconstructed this transformation in the course of philosophy known as the Linguistic Turning has had a clear impact and formed a cognitive background for many linguistic approaches and their theories. Through this study, we try to highlight the achievements of this analytical trend and its reflection on language and linguistics and its theories, especially theories of meaning.